Driving electrocatalytic activity by interface electronic structure control in a metalloprotein hybrid catalyst for efficient hydrogen evolution. Issue 33 (8th August 2016) - Behera, Sushant Kumar; Deb, Pritam; Ghosh, Arghya
Abstract : Schematic presentation of a silver incorporated lysine-216 (LYS-216) active site bonded with the retinal chromophore (RC) of bacteriorhodopsin (bR) bacteria for the hydrogen evolution reaction. Abstract : The rational design of metalloprotein hybrid structures and precise calculations for understanding the role of the interfacial electronic structure in regulating the HER activity of water splitting sites and their microscopic effect for obtaining robust hydrogen evolution possess great promise for developing highly efficient nano-bio hybrid HER catalysts. Here, we employ high-accuracy linear-scaling density functional theory calculations using a near-complete basis set and a minimal parameter implicit solvent model within the self-consistent calculations, on silver (Ag) ions assimilated on bacteriorhodopsin (bR) at specific binding sites. Geometry optimization indicates the formation of active sites at the interface of the metalloprotein complex and the density of states reflects the metallic nature of the active sites. The reduced value of the canonical orbital gap indicates the state of dynamic nature after Ag ion assimilation on active sites and smooth electron transfer. These incorporated active protein sites are more efficient in electrolytic splitting of water than pristine sites due to their low value of Gibbs free energy for the HER in terms of hydrogen coverages. Volcano plot analysis and the free energy diagram are compared for understanding the hydrogen evolution efficiency. Moreover, the essential role of the interfacial electronic properties in regulating the HER catalytic activity of water splitting sites and enhancing the efficiency is elucidated.